Effect of Coaching Behaviors on Team Cohesion and Performance in Iraqi Premier League - Jabar Matar AL-Bkhati, Maytham; Aziz Dawood Al-Sudani, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to examine the effect of coaching behaviors on team cohesion and performance in the Iraqi Premier League in the 2017-2018 season. It is descriptive research of correlation type, and a field survey was used for data collection. The population includes 440 players in the form of 20 teams that 205 players chose as a sample based on Morgan's table. In order to collect data, the Coaching Behavior Questionnaire (CBQ; Martin & Barnes, 1999) and Team Cohesion Questionnaire (GEQ; Carron, Widmeyer, & Brawley, 1985) were used. For measuring the performance of Iraqi football teams, their rank in the table was used as a criterion. Instrument reliability was obtained using Cronbach's alpha (coaching behavior: 0.75, cohesion: 0.83). Research tool validity was confirmed using expert ideas and confirmatory factor analysis in AMOS software. Descriptive statistics (central tendency, dispersion) and inferential statistics (Structural Equation Modeling—AMOS software) were used for data analysis. Results showed that positive reactive coaching behaviors had a significant impact on team cohesion and performance. However, normal coaching behavior had no significant impact, and negative reactive coaching behavior had no significant impact on the team performance.